Investigation of Trace Element Levels and Toxic Metals in Obese Children: A Single-Center Experience - Sultan Kaba; Sinan Kılıç (Turkish Archives of Pediatrics)
Objective: The complete role of factors contributing to the pathogenesis of childhood obesity remains to be fully elucidated. Limited research has addressed trace elements in the context of child obesity. Our objective was to assess trace element and lead (Pb), copper (Cu) (are toxic metal) levels in both healthy and obese children, and to investigate the potential correlations between these elements and obesity-related anthropometric measurements, lipid profiles, as well as insulin and glucose levels.